Asta Wirat Bhumi’s Music Intrument | Gamelan Asta Wirat Bhumi - Putu Tiodore Adi Bawa (GHURNITA: Jurnal Seni Karawitan, 2022)
Creation in Balinese music becomes very interesting when the exploration of tools and ideas is poured together. Asta Wirat Bhumi cultivation process using the theory of creation by Alma M. Hawkins comprising the steps of exploration, improvisation, and formation. Asta Wirat Bhumi can be seen from two sides, namely as a new gamelan and as an experimental piece of music. Asta Wirat Bhumi as a new gamelan is the result of the process of three types of Balinese gamelan namely Balaganjur, Jegog, and Selonding starting from the exploration process, improvisation, to the formation process. The three types of gamelan are mixed into a new barungan gamelan with a successful arrangement of instruments, characters, tones, techniques, and patets. While Asta Wirat Bhumi is a reflection of the reception of Lontar Tutur Bhuwana Mabah as the idea of a musical work as outlined in the gamelan Asta Wirat Bhumi. The process of activities starting from exploration, improvisation, and formation becomes a reference in an enhanced framework with the stages of inspiration. Reflection and reception were chosen as a technique to understand the text as the idea of Asta Wirat Bhumi's musical work which is contained in the form/structure of the song and the performance of the work. The results obtained in the form of experimental music "Asta Wirat Bhumi" by casting in the new gamelan "Asta Wirat Bhumi" brought a message to the audience.